Health-related quality of life profiles in patients with rheumatoid arthritis: a latent profile analysis - Song, Yuqing; Chen, Yanling; Wen, Liting; He, Benyi; Ding, Yulin; Liu, Mei; Tang, Fangmei; Wang, Li; Wu, Jianmei; Deng, Xue; Xing, Lu; Zhao, Wen (Frontiers in Public Health, 2024)
BackgroundRheumatoid arthritis (RA) is a common rheumatic disease that most commonly affects joints and negatively impacts individuals’ health-related quality of life (HRQoL). Although some studies have explored HRQoL of RA patients, existing studies treated RA patients as a homogeneous group based on their overall HRQoL and ignore the heterogeneity of patients’ HRQoL patterns. This study aimed to identify subgroups of RA patients based on their HRQoL and variables associated with group membership.MethodsThis was a multi-center cross-sectional study conducted at 3 tertiary hospitals. All participants completed standardized questionnaires including demographic variables, HRQoL, physical function, disease activity and self-efficacy. Latent profile analysis was used to identify the optimal number of subgroups (profiles) and multinomial logistic regression analysis was used to explore variables associated with profile membership.ResultsThe analysis revealed 3 profiles of RA patients: poor HRQoL (N = 92, 60.9%), moderate HRQoL but poor role function (N = 45, 29.8%), good HRQoL (N = 14, 9.3%). Regression analysis revealed that patients with worse physical function were more likely to belong to “poor HRQoL” and “moderate HRQoL but poor role function” profile. Additionally, patients with junior high school or below educational level were less likely to belong to “moderate HRQoL but poor role function” profile.ConclusionThis study identified 3 profiles of HRQoL within RA patients and found that physical function and educational level was associated with HRQoL profiles. The finding can provide the basis for developing tailored interventions to specific subgroups of RA patients.